2019
DOI: 10.4269/ajtmh.18-0632
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sanitation and Hygiene through Community-Led Total Sanitation: The Zambian Experience

Abstract: In 2012, approximately 5.6 million Zambians did not have access to improved sanitation and around 2.1 million practiced open defecation. The Zambia Sanitation and Hygiene Program (ZSHP), featuring community-led total sanitation, began in November 2011 to increase the use of improved sanitation facilities and adopt positive hygiene practices. Using a pre-and post-design approach with a population-level survey, after 3 years of implementation, we evaluated the impact of ZSHP in randomly selected households in 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Individually-oriented interventions focused on behavior change leave households accountable for the failure to adopt safe sanitation practices. Education and social marketing have been only modestly successful in the sustained reduction of OD in India or elsewhere [34,50]. Behavior change interventions have also been critiqued because, for those who cannot change their behavior due to structural reasons, they generate "additional social stigma for failing to maintain new social norms regarding health behaviors" [36] (p. 194).…”
Section: Discussionmentioning
confidence: 99%
“…Individually-oriented interventions focused on behavior change leave households accountable for the failure to adopt safe sanitation practices. Education and social marketing have been only modestly successful in the sustained reduction of OD in India or elsewhere [34,50]. Behavior change interventions have also been critiqued because, for those who cannot change their behavior due to structural reasons, they generate "additional social stigma for failing to maintain new social norms regarding health behaviors" [36] (p. 194).…”
Section: Discussionmentioning
confidence: 99%
“…A program such as Community-Based Total Sanitation (CBTS) will increase the latrine ownership of each household by at least twice the percentage, which was evident from a study conducted in Ghana and Tanzania. Likewise, based on the findings in Mali, there was a decrease of at least 24% for people who practice open defecation (20). Similar studies in Indonesia showed that in the CBTS program, especially the aspect of not practicing open defecation had a relationship with diarrhea (2,17).…”
Section: Discussionmentioning
confidence: 90%
“…Though the program is in implementation, availability and proper use of latrines, water, and hand washing facilities remains low in Ethiopia. The approach requires enhanced investments and amplified efforts across the WASH sector to deliver strong outcomes [ 29 , 30 , 31 ]. Similarly, Ethiopia’s 2017–2022 Growth and Transformational Plan (GTP) centers WASH, inclusion, and the needs of women, youth, and vulnerable people, however the intended results remain well behind targets.…”
Section: Introductionmentioning
confidence: 99%